D-Map: Visual analysis of ego-centric information diffusion patterns in social media - Siming Chen; Shuai Chen; Zhenhuang Wang; Jie Liang; Xiaoru Yuan; Nan Cao; Yadong Wu (VAST'16: Proceedings of the IEEE Conference on Visual Analytics Science and Technology, 2016)
Popular social media platforms could rapidly propagate vital information over social networks among a significant number of people. In this work we present D-Map (Diffusion Map), a novel visualization method to support exploration and analysis of social behaviors during such information diffusion and propagation on typical social media through a map metaphor. In D-Map, users who participated in reposting (i.e., resending a message initially posted by others) one central user's posts (i.e., a series of original tweets) are collected and mapped to a hexagonal grid based on their behavior similarities and in chronological order of the repostings. With additional interaction and linking, D-Map is capable of providing visual portraits of the influential users and describing their social behaviors. A comprehensive visual analysis system is developed to support interactive exploration with D-Map. We evaluate our work with real world social media data and find interesting patterns among users. Key players, important information diffusion paths, and interactions among social communities can be identified.